2010
DOI: 10.1002/14651858.cd007310.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Cervical preparation for second trimester dilation and evacuation

Abstract: Cervical preparation with osmotic dilators and/or misoprostol before second-trimester D&E is safe and effective. Osmotic dilators appear to provide superior cervical dilation when compared to prostaglandins alone or when combined with prostaglandins, however this difference in cervical dilation does not appear to result in differences in procedure time or complication rates. There does not appear to be clear clinical benefit from two days of cervical preparation compared to one-day prior to second-trimester D&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 30 publications
0
19
0
2
Order By: Relevance
“…This is accomplished with use of a series of laminaria tents, synthetic osmotic dilators, or a prostaglandin analogue, misoprostol. 4 The D&E procedure may be performed under any level of anesthesia, depending upon procedure location, patient tolerance, medical comorbidities, and gestational age. The fetal and placental tissue is then evacuated using a combination of suction and extraction forceps in multiple passes.…”
Section: Definition Of Dande and Indicationsmentioning
confidence: 99%
“…This is accomplished with use of a series of laminaria tents, synthetic osmotic dilators, or a prostaglandin analogue, misoprostol. 4 The D&E procedure may be performed under any level of anesthesia, depending upon procedure location, patient tolerance, medical comorbidities, and gestational age. The fetal and placental tissue is then evacuated using a combination of suction and extraction forceps in multiple passes.…”
Section: Definition Of Dande and Indicationsmentioning
confidence: 99%
“…Second trimester abortion by dilation and evacuation (D&E) requires greater cervical dilation than first trimester procedures; to improve safety the dilation is commonly done by placement of osmotic dilators such as laminaria one or two days before the D&E procedure [1][2][3]. Many women find laminaria placement painful if no anesthesia is used [4,5]; several studies have reported that the procedure may be associated with moderate to severe pain even when cervical or paracervical block is performed [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A third alternative for cervical priming is the administration of mifepristone 200 mg, but this has the disadvantage of higher cost as well as more clinic visits by the patient; also another effect of mifepristone is the possibility of expulsion of the fetus before D & E, with the consequent risk to the woman's health, as this expulsion may occur at any time and place [8]. A Cochrane Review in 2010 concluded that mifepristone is associated with high rates of pre-procedural expulsions and does not appear to be a useful method of cervical preparation before second-trimester dilation and evacuation [9].…”
Section: Discussionmentioning
confidence: 99%